2021
DOI: 10.3389/fcvm.2021.732349
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Obstructive Pulmonary Disease With Arrhythmia Risks: A Systematic Review and Meta-Analysis

Abstract: Background: A large number of studies have shown that the arrhythmia risks may be the potential causes of death among chronic obstructive pulmonary disease (COPD) patients. However, the association of COPD with risks of arrhythmias has never been systematically reviewed. Therefore, we performed a meta-analysis to assess the relationship between COPD and arrhythmia risks.Methods: An updated systematic retrieval was carried out within the databases of Embase and PubMed until June 27, 2021.The random-effects mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…For example, patients with chronic obstructive pulmonary disease demonstrate abnormal heart rate recovery after exercise ( 10 ). The prevalence of cardiac arrhythmias, especially atrial fibrillation, where vagal neurotransmission plays an important role, is increased in these patients ( 11 ). Conversely, Cheyne-Stroke respiration and sleep apnea are associated with the occurrence of atrial fibrillation and increased mortality in the setting of heart failure ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, patients with chronic obstructive pulmonary disease demonstrate abnormal heart rate recovery after exercise ( 10 ). The prevalence of cardiac arrhythmias, especially atrial fibrillation, where vagal neurotransmission plays an important role, is increased in these patients ( 11 ). Conversely, Cheyne-Stroke respiration and sleep apnea are associated with the occurrence of atrial fibrillation and increased mortality in the setting of heart failure ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Наличие сочетанной кардиореспираторной патологии не только ухудшает течение и прогноз у пациентов, но и вызывает большие сложности в подборе медикаментозной терапии. Так, β2-агонисты являются крае угольным камнем в лечении пациентов с бронхообструктивной патологией [7], однако, несмотря на большое количество проведенных исследований, доказавших их эффективность, до настоящего времени существуют противоречивые данные относительно безопасности использования бронходилататоров при сердечно-сосудистых заболеваниях [8].…”
Section: оригинальное исследованиеunclassified
“…Additionally, COPD patients frequently experience cardiac arrhythmias [ 11 , 55 ], and atrial fibrillation is often observed during AECOPD [ 11 , 56 ]. Furthermore, the prevalence of peripheral artery disease is higher in COPD patients compared to the general population and is commonly associated with atherosclerotic heart disease [ 11 , 57 ].…”
Section: Introductionmentioning
confidence: 99%